2001
DOI: 10.1007/s004640080199
|View full text |Cite
|
Sign up to set email alerts
|

Higher colon cancer tumor proliferative index and lower tumor cell death rate in mice undergoing laparotomy versus insufflation

Abstract: We have demonstrated that there is a significantly higher rate of tumor cell proliferation and a significantly lower rate of tumor cell death with the C-26 colon adenocarcinoma tumor line after laparotomy than after insufflation or anesthesia alone on post-operative day 14. The mechanisms of these phenomena are unclear. It appears that certain factors postoperatively stimulate tumors to proliferate at a higher rate, causing tumor cells to die at a lower rate in the laparotomy group than in the insufflation gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…The results of experimental studies on the behavior of tumor cells exposed to CO2 are not conclusive. Numerous authors confirmed a CO2 associated increase of tumor growth and invasiveness of various cell lines derived from colon carcinoma, adenocarcinoma, and other tumors using animal models [18][19][20] . However, other studies showed that CO2 pneumoperitoneum could increase cell necrosis and decrease proliferation [8,21] .…”
Section: Discussionmentioning
confidence: 87%
“…The results of experimental studies on the behavior of tumor cells exposed to CO2 are not conclusive. Numerous authors confirmed a CO2 associated increase of tumor growth and invasiveness of various cell lines derived from colon carcinoma, adenocarcinoma, and other tumors using animal models [18][19][20] . However, other studies showed that CO2 pneumoperitoneum could increase cell necrosis and decrease proliferation [8,21] .…”
Section: Discussionmentioning
confidence: 87%
“…7 Apparently, the same difficulties of comparison arise as the situation of total hepatic cancerous affection seems to differ from the state of solitary metastases, and semiquantitative measures are unequal to the quantitative stereological measures of the present study. A favourable oncological outcome after CO 2 laparoscopy was detected by Bouvy et al 10 and Lee et al 11 Bouvy administered the tumour cells both into the abdominal cavity and under the renal capsule, omitting the haematogeneous factor and focusing on a well-localisable subcapsular renal tumour nodule. Interestingly, subcapsular injection and consecutive elevated intra-abdominal pressures resulted in less severe tumour growth than did open surgery, although Bouvy used the kidney instead of the liver and thus focused on a retroperitoneal site.…”
Section: Discussionmentioning
confidence: 98%
“…A couple of experimental studies have assessed the influence of laparoscopy on postoperative outcome of colorectal carcinoma using various models. The assessment of haematogeneous hepatic tumour spread in rats 7,8 and mice 9 and of renal or cutaneous tumour growth after subcapsular 10 or subcutaneous 11 injection of colorectal carcinoma cells have led to controversial for and against arguments for the laparoscopic technique. Importantly, hepatic macrophages have been described as playing a key oncological role in cellular antitumoural defence in respect of enhanced experimental tumour growth following selective depletion of phagocytotic cells.…”
mentioning
confidence: 99%
“…However, several reports show that surgical stress possibly enhances the growth of the dormant malignant cells [3,25,26] . Also, the mechanisms by which surgical trauma might enhance tumor growth and metastasis still are not totally understood [3,4,27].…”
Section: Discussionmentioning
confidence: 98%
“…In clinical settings, tumor recurrence may be explained by the residual microscopic cancer cells after surgical resection [25,26]. Even after complete resection of primary and secondary hepatic malignancies, recurrent disease develops in nearly two-thirds of patients, and it is believed to arise from residual microscopic cancer undetected at surgery [32].…”
Section: Discussionmentioning
confidence: 99%